General Reaction Score and CD56+CD16+CD3- Cells Distributions Among Women with Aircraft Noise Stress - Hartono Hartono (MEDIA MEDIKA INDONESIANA, 2011)
ABSTRACTBackground: One of the noise impacts is stress. The NK cells (CD56+CD16+CD3-) are also one of the leukocyte subsets, which are responsive to the physiological stress and psychological stress. The aims of the research is to find out the correlation of the general reaction score with CD56+CD16+CD3- cells distributions among women with aircraft noise stress in the area of Adi Sumarmo Airport of Solo, Indonesia.Methods: The research design was an analytical survey with a cross sectional approach, taking location at the Dibal and Gagak Sipat Village, Boyolali District. The respondents who fulfilled the exclusive and inclusive criteria were selected by means of simple random sampling. The number of respondens was 39 and divided into 3 groups; Group 1 was exposed 92.29 dB of noise level (13 respondents); Group 2 was exposed 71.79 dB of noise level (13 respondents); and Group 3 was exposed 52.17 dB of noise level (13 respondents). The data were analyzed by Anova followed by post hoc test using LSD test completed with homogenous subsets and Pearson Correlation test.Results: The Pearson Correlation test was showed that there was significant association between general reaction score with CD56+CD16+CD3- cells distributions (r=0.589; p=0.000).Conclusion: There is correlation of the general reaction score with CD56+CD16+CD3- cells distributions among women with aircraft noise stress in the area of Adi Sumarmo Airport of Solo, Indonesia.Keywords: Aircraft noise, CD56+CD16+CD3-, women, Adi Sumarmo AirportABSTRAKGeneral Reaction Score dan CD56+CD16+CD3- pada wanita yang mengalami stres bising pesawat udaraLatar belakang: Salah satu dampak bising adalah stres. Natural killer cells (CD56+CD16+CD3-) adalah salah satu subset leukosit yang sangat respon terhadap stres fisiologis maupun stres psikologis. Tujuan penelitian adalah untuk mengetahui hubungan antara general reaction score dengan jumlah sel NK (CD56+CD16+CD3-) pada wanita yang memperoleh stres bising pesawat udara disekitar Bandara Adi Sumarmo Solo, Indonesia.Metode: Rancangan penelitian adalah survai analitik dengan pendekatan cross sectional. Lokasi di Desa Dibal dan Gagak Sipat, Kabupaten Boyolali. Responden yang memenuhi kriteria eksklusif dan inklusif diambil sejumlah 39 sebagai sampel dengan cara simple random sampling. Responden selanjutnya dibagi menjadi 3 kelompok; Kelompok 1 responden yang terpapar bising denganintensitas 92,29 dB (13 responden); Kelompok 2 responden yang terpapar bising dengan intensitas 71.79 dB (13 responden); dan Kelompok 3 responden yang terpapar bising dengan intensitas 52.17 dB (13 responden). Data dianalisis dengan uji Anova dilanjutkan dengan post hoc test menggunakan LSD test completed with homogenous subsets dan Pearson Correlation test.Hasil: Pearson Correlation test menunjukkan adanya hubungan yang signifikan antara general reaction score dengan jumlah sel NK (CD56+CD16+CD3-) (r=0.589: p=0.000).Simpulan: Penelitian ini menunjukkan bahwa ada hubungan antara general reaction score dengan jumlah sel NK(CD56+CD16+CD3-) pada wanita yang mengalami stres bising pesawat udara di sekitar Bandara Adi Sumarmo Solo, Indonesia.